(untitled) - Curran, Michael G. (New York, 2002)
Accounting Fundamentals is a text-kit that provides a brief but comprehensive introduction to accounting. It gives students a. basic understanding of accounting principles and procedures used for recording, classifying,. and summarizing financial data. Students also learn accounting terminology and are introduced to the financial forms, records, and statements used in the. business world.
Keywords: Accounting